No Correlation between Biofilm Formation, Virulence Factors, and Antibiotic Resistance in Pseudomonas aeruginosa: Results from a Laboratory-Based In Vitro Study - Márió Gajdács; Zoltán Baráth; Krisztina Kárpáti; Dóra Szabó; Donatella Usai; Stefania Zanetti; Matthew Gavino Donadu (MDPI AG, 2021)
Pseudomonas aeruginosa (P. aeruginosa) possesses a plethora of virulence determinants, including the production of biofilm, pigments, exotoxins, proteases, flagella, and secretion systems. The aim of our present study was to establish the relationship between biofilm-forming capacity, the expression of some important virulence factors, and the multidrug-resistant (MDR) phenotype in P. aeruginosa. A total of three hundred and two (n = 302) isolates were included in this study. Antimicrobial susceptibility testing and phenotypic detection of resistance determinants were carried out; based on these results, isolates were grouped into distinct resistotypes and multiple antibiotic resistance (MAR) indices were calculated. The capacity of isolates to produce biofilm was assessed using a crystal violet microtiter-plate based method. Motility (swimming, swarming, and twitching) and pigment-production (pyoverdine and pyocyanin) were also measured. Pearson correlation coefficients (r) were calculated to determine for antimicrobial resistance, biofilm-formation, and expression of other virulence factors. Resistance rates were the highest for ceftazidime (56.95%; n = 172), levofloxacin (54.97%; n = 166), and ciprofloxacin (54.64%; n = 159), while lowest for colistin (1.66%; n = 5); 44.04% (n = 133) of isolates were classified as MDR. 19.87% (n = 60), 20.86% (n = 63) and 59.27% (n = 179) were classified as weak, moderate, and strong biofilm producers, respectively. With the exception of pyocyanin production (0.371 ± 0.193 vs. non-MDR: 0.319 ± 0.191; p = 0.018), MDR and non-MDR isolates did not show significant differences in expression of virulence factors. Additionally, no relevant correlations were seen between the rate of biofilm formation, pigment production, or motility. Data on interplay between the presence and mechanisms of drug resistance with those of biofilm formation and virulence is crucial to address chronic bacterial infections and to provide strategies for their management.